Spatial Variability of Explosive Blast Loading and its Effect on Disproportionate Collapse Risks - Stewart, Mark; ICASP14 (My University, 2023)
Disproportionate collapse is often triggered by malevolent or accidental explosive blast loading. Explosive blast loading is subject to inherent variabilities due to complex interactions between chemical reactions, air particles, fireball and shockwave. Explosive field trials have quantified this variability, and described herein is the probabilistic characterisation of spatial variability of airblast for pressure and impulse. In other words, pressure-time measurements from adjacent (close) gauges are not identical, but correlated based on the distance between the gauges. The degree of correlation is moderate if distance between gauges is small, and reduces to a weak correlation for gauges spaced much further apart. The effect of spatial variability of airblast on damage and collapse risks is investigated for a 10 storey reinforced concrete building subject to a vehicle borne improved explosive device (VBIED) attack, and the accidental detonation of explosive ordnance (EO). The structural reliability analysis considered load redistribution for failed columns, dead and live loading variabilities, and blast loading and resistance model errors. It was found that allowing for the spatial variability of airblast decreased disproportionate collapse probabilities by up to16-33% when compared to the case of fully correlated airblast. Designing against disproportionate collapse reduced damage risks by over 99%.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED